2015
DOI: 10.1371/journal.pone.0115350
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pancreatic Beta Cell Exposure to High Levels of Glucose but Not Palmitate Induces DNA Methylation within the Insulin Gene Promoter and Represses Transcriptional Activity

Abstract: Recent studies have implicated epigenetics in the pathophysiology of diabetes. Furthermore, DNA methylation, which irreversibly deactivates gene transcription, of the insulin promoter, particularly the cAMP response element, is increased in diabetes patients. However, the underlying mechanism remains unclear. We aimed to investigate insulin promoter DNA methylation in an over-nutrition state. INS-1 cells, the rat pancreatic beta cell line, were cultured under normal-culture-glucose (11.2 mmol/l) or experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…The ‘metabolic memory’ that persists following glucose control of diabetes is also postulated to be due to epigenetic modifications in endothelial cells [8]. Ishikawa et al reported that long-term, high levels of glucose induce DNA methylation in INS-1 cells [9]. Several other studies have also shown epigenetic modifications in diabetes and after glucose treatment [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘metabolic memory’ that persists following glucose control of diabetes is also postulated to be due to epigenetic modifications in endothelial cells [8]. Ishikawa et al reported that long-term, high levels of glucose induce DNA methylation in INS-1 cells [9]. Several other studies have also shown epigenetic modifications in diabetes and after glucose treatment [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study found an increase in DNA methyl transferase activity, Dnmt1 expression, and decreased TET activity (Ishikawa, Tsunekawa et al 2015). It is Page 20 of 42…”
Section: Hyperglycemiamentioning
confidence: 89%
“…In a recent study, Ishikawa et al reported that long-term exposure of pancreatic beta cells to a HG state increased DNA methylation of the insulin gene ( Ins1 ) promoter at the CRE site that is important for insulin gene transcription32. Seman et al also showed that increased DNA methylation of the promoter of the SLC30A8 gene, the product of which is essential for the transportation of zinc into the insulin-secretory granules and the subsequent crystallization of hexameric insulin, is associated with type 2 diabetes33.…”
Section: Discussionmentioning
confidence: 99%